2019
DOI: 10.1002/mus.26659
|View full text |Cite
|
Sign up to set email alerts
|

Comparing electrical stimulation and tacrolimus (FK506) to enhance treating nerve injuries

Abstract: Introduction Neuroenhancing therapies are desired because repair of nerve injuries can fail to achieve recovery. We compared two neuroenhancing therapies, electrical stimulation (ES) and systemic tacrolimus (FK506), for their capabilities to enhance regeneration in the context of a rat model. Methods Rats were randomized to four groups: ES 0.5 mA, ES 2.0 mA, FK506, and repair alone. All groups underwent tibial nerve transection and repair, and outcomes were assessed by using twice per week walking track analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…46 Both of these evaluations were similar between the control and ES groups, suggesting that short-term ES did not adversely affect the regenerating nerves, which is consistent with a study published in the literature that demonstrated no adverse effects within the nerve histology 3 days postoperative after a 1-h procedure using intraoperative ES. 45 Although muscle atrophy was observed at the 6-week time-point and significantly reduced after 12 weeks, ES did not show any significant effect on muscle atrophy compared with the control.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…46 Both of these evaluations were similar between the control and ES groups, suggesting that short-term ES did not adversely affect the regenerating nerves, which is consistent with a study published in the literature that demonstrated no adverse effects within the nerve histology 3 days postoperative after a 1-h procedure using intraoperative ES. 45 Although muscle atrophy was observed at the 6-week time-point and significantly reduced after 12 weeks, ES did not show any significant effect on muscle atrophy compared with the control.…”
Section: Discussionmentioning
confidence: 76%
“…However, the similarity in functional responses between the groups agreed with the literature in showing that ES did not negatively affect the motor and sensory recovery of the nerve. 45 To investigate the effect of ES at the tissue level, nerve regeneration and muscle atrophy were assessed through histology evaluations. Percent nerve and mean fiber width are parameters that indicate the quality and maturity of regenerating nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, systemic toxicity is a key limiting factor for tacrolimus in the context of peripheral nerve surgery 42 . By generating a local and sustained, low-dose release profile, the monthly cumulative tacrolimus dose was reduced by more than 98% (200 µg vs 15.5 mg) when compared to previously established systemic drug delivery regimen for promoting nerve regeneration 52,53 . Accordingly, the tacrolimus plasma concentration following local delivery was significantly lower when compared to systemic application, and maximum and average plasma levels remained well below the trough concentration (Cmin) of systemically treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings that tacrolimus released form the nerve wrap promoted neurite outgrowth in vitro, we asked whether repaired nerves regenerate more axons when the nerve wrap is implanted around the coaptation site. We transected the common peroneal nerve in rats followed by immediate epineural repair, and either implanted a tacrolimus nerve wrap (200 µg per wrap) or subcutaneously injected tacrolimus daily after surgery (2 mg/kg bodyweight) as previously described 52,53 . Rats that received a vehicle wrap or nerve repair only served as controls.…”
Section: Tacrolimus Nerve Wrap Implantation Increases the Number Of Regenerating Nerve Fibers Following Nerve Repairmentioning
confidence: 99%
“…Electrical stimulation also induces a 2.3-fold increase in the extent of axon sprouting from transected axons [105] while increasing the speed of axon regeneration [101,103,106]. At the same time, in animal models, electrical stimulation increases the distance axons regenerate across nerve gaps, the accuracy of sensory vs. motor axon innervation of their appropriate targets, and extent of functional recovery [107][108][109][110]. Electrical stimulation of peripheral nerve clinically also induces enhanced axon regeneration [102].…”
Section: Promoting Axotomized Neurons To Extend Axonsmentioning
confidence: 99%